Legal Frameworks for Tertiary Education in Sub-Saharan Africa : The Quest for Institutional Responsiveness - Saint, William; Lao, Christine; Materu, Peter (Washington, DC: World Bank, 2013)
Prospects for future economic growth in Sub-Saharan Africa will depend in significant measure on the continent's capacity to cultivate the higher order skills and expertise needed to acquire knowledge and utilize it to advance economic and social development. Recognition of this reality is leading policy makers and politicians across the region to renew their attention to the role that tertiary education can play in undergirding knowledge-based strategies for growth and competitiveness. As this awareness has grown, fuller understanding of the relationship between human capital formation and economic growth, the types of tertiary education policies that can nurture this relationship, and the national-level conditions that shape the possibilities for success in these endeavors has been pursued by the World Bank through a series of analytical studies. This analytical work culminated in 2008 with the completion of the region's flagship report entitled accelerating catch-up: tertiary education for growth in Sub-Saharan Africa. This report examined the human resource implications of more knowledge-intensive strategies for growth in Africa within the context of globalize competition and argued the need for more conscious management of education policies in order to align education sector outputs, especially postsecondary graduates and research, with national strategies for economic growth and poverty alleviation. In doing so, the report issued a clear call for more autonomous, flexible, and responsive institutions of tertiary education capable of adjusting their missions and programs to fast-paced changes in the technologies, economic relations, and trade regimes that can spell the difference between a nation's competitiveness and stagnation within the global economic arena. It also highlighted the critical role of governance arrangements at the level of tertiary education systems as well as individual tertiary institutions in determining capabilities for flexibility and responsiveness that enable timely adaptation to change.